Initial psychometric properties of the Perceived Stress Scale for Kids (PeSSKi) in a sample of Polish children - Sara Filipiak; Anna Hawrot; Christina Davis; Constantina Panourgia; Julie Gamble-Turner (Journal of Health Psychology, 2026)
The aim of this study was to establish the psychometric properties of the Polish version of the Perceived Stress Scale for Kids (PeSSKi). The procedure included assessment of the PeSSKi’s theoretical and discriminant validity. A total of 334 child-guardian dyads were recruited from public elementary schools. Children were in the age range 9–11 years (M age = 10 years). Participants completed the following questionnaires: the self-report and parent-report version of the Strengths and Difficulties Questionnaire, parent-report version of the Profile of Emotional and Social Development and Student Integration Questionnaire. Analyses indicated that although specific valence facets were present, the Polish version of the PeSSKi was essentially unidimensional. Correlational analysis of the Polish PeSSKi with related constructs suggested satisfactory convergent and discriminant validity supporting its potential usefulness as a unidimensional measure of perceived stress in children aged 9–11 years.